Sustainability in Urban Planning and Design - Almusaed, Amjad; Almssad, Asaad; Truong - Hong, Linh (IntechOpen, 2020)
This book has been prepared to embody the major and efficient applications of the different duties and the role of sustainability in urban planning and design, by a new reading of the city structure and composition, as well as offering a solid and clear concept for this kind of science. The book aims to illustrate various theories and methods of the treatment of the modern ideas of metropolitan life. The book is divided into two parts and contains 23 chapters.